The Health Care Pattern and The Diversity of Animal Protein Sources In Stunting and Non-Stunting Under Two Years Children In East Kalimantan (Cuestiones de Fisioterapia, 2025)
The Stunting is still a major problem in child health in East Kalimantan Province. Various prevention andmanagement efforts have been carried out through specific and sensitive interventions. Even so, thecomplex determinants of stunting risk still require further analysis, especially regarding parentingpractices in families with under two years of age children. This was an observational study with a casecontrol design. The sample in this study were mothers who had under-two years of age children who livedin the selected stunting locus, in North Penajam Paser, East Kutai, and Kutai Kartanegara Regencies. Datawere obtained from 88 children (cases) and 171 children (controls). Health care pattern data were analyzedby Mann Whitney test and child’s feeding pattern was analyzed by the Chi-square test. This study showedthat there was a difference in the scores for health care (p-value <0.01) and child feeding pattern (pvalue=0.02) between families of under-two years of age children who are not stunted and those who arestunted.